2018
DOI: 10.1002/anie.201808289
|View full text |Cite
|
Sign up to set email alerts
|

C2‐Symmetric Bicyclic Bisborane Catalysts: Kinetic or Thermodynamic Products of a Reversible Hydroboration of Dienes

Abstract: We prepared a new class of chiral C -symmetric bicyclic bisborane catalysts by addition reactions of internal dienes with the Piers borane, HB(C F ) , and an analogue, HB(p-C F H) . The dependence of the addition pattern on the reaction temperature allowed us to selectively prepare two diastereomeric catalysts from a single diene precursor. The bisboranes prepared in situ exhibited excellent activity (turnover numbers up to 200 at -40 °C) and enantioselectivity (up to 95 % ee) in imine hydrogenation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Recently, we developed a series of chiral C 2 ‐symmetric bisborane catalysts that are prepared by hydroboration reactions of bicyclic [3.3.0] dienes with HB(C 6 F 5 ) 2 and HB( p ‐C 6 F 4 H) 2 . These catalysts are highly effective and selective in asymmetric imine hydrogenations.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, we developed a series of chiral C 2 ‐symmetric bisborane catalysts that are prepared by hydroboration reactions of bicyclic [3.3.0] dienes with HB(C 6 F 5 ) 2 and HB( p ‐C 6 F 4 H) 2 . These catalysts are highly effective and selective in asymmetric imine hydrogenations.…”
Section: Methodsmentioning
confidence: 98%
“…X‐ray crystallographic analyses revealed that the aryl groups were trans to the B(C 6 F 5 ) 2 groups in both cyclopentane rings and that the overall structures were C 2 ‐symmetric . Notably, unlike hydroboration reactions of bicyclic [3.3.0] dienes, these hydroborations gave the same isomers when they were performed at higher temperatures (e.g., 80 °C).…”
Section: Methodsmentioning
confidence: 99%
“…106 Very recently, Peng and Wang reported the conversion of chiral diene (S,S)-140a through hydroboration into the bicyclic bisboranes 150a and 150b, which were employed as organocatalysts for the hydrogenation of imines 151 (Scheme 42). 107…”
Section: Account Synlettmentioning
confidence: 99%
“…Gratifyingly, under these conditions, the loading of 1 a could be decreased to 1 mol %, the yield of P1' improved to 88 %, and the enantioselectivity improved to 91 % ee (entry 11). Three bisborane catalysts with other substituted aryl rings (1 b-1 d) failed to give better results than 1 a (entries [12][13][14], and B(C 6 F 5 ) 3 (10 mol %) was completely inactive under these conditions (entry 15). The high activity and high turnover numbers obtained with the spiro-bicyclic bisborane catalysts may be attributable to the steric bulk around the boron atom, which not only permits Lewis acid activation of HBpin at ambient temperature by destabilizing the complex between the pyridine substrate and the catalyst (for the overall reaction mechanism, see Figure S1 in the supporting information) but also enhances the chemostability of the catalyst by preventing the attack of other nucleophiles (that is, other than hydride) at the Lewis acidic boron.…”
mentioning
confidence: 99%
“…[8] Research in this area has resulted in breakthroughs in enantioselective hydrogenations of imines and quinolines catalyzed by chiral boranes. [9][10][11][12] The major advantage of these reactions over conventional transition-metal-catalyzed hydrogenation is the excellent chemoselectivity. In particular, the reactions have been found to occur highly selectively at very polarized p bonds (e.g., imines and enamines) while leaving many other unsaturated functional groups (including olefins, alkynes, and carbonyl groups) intact.…”
mentioning
confidence: 99%